Impact on the NHS and health of the UK's trade and cooperation relationship with the EU, and beyond. Issue 4 (28th October 2022) - Fahy, Nick; Hervey, Tamara; Dayan, Mark; Flear, Mark; Galsworthy, Michael J.; Greer, Scott; Jarman, Holly; McCarey, Martha; McKee, Martin; Wood, Matthew
Abstract: The UK's relationship with the European Union (EU) is now embodied in two principal legal instruments: the EU–UK Trade and Cooperation Agreement, which formally entered into force on 1 May 2021; and the Withdrawal Agreement, with its Protocol on Ireland/Northern Ireland, which continues to apply. Using a 'building blocks' framework for analysis of national health systems derived from the World Health Organisation, this article examines the likely impacts in the UK of this legal settlement on the National Health Service (NHS), health and social care. Specifically, we determine the extent to which the trade, cooperation and regulatory aspects of those legal measures support positive impacts for the NHS and social care. We show that, as there is clear support for positive health and care outcomes in only one of the 17 NHS 'building blocks', unless mitigating action is taken, the likely outcomes will be detrimental. However, as the legal settlement gives the UK a great deal of regulatory freedom, especially in Great Britain, we argue that it is crucial to track the effects of proposed new health and social care-related policy choices in the months and years ahead.